Martha's flowers : a practical guide to growing, gathering, and enjoying - Stewart, Martha; Sharkey, Kevin (Clarkson Potter Publishers, an imprint of the Crown Publishing Group, 2018)
"Martha Stewart's lifelong love of flowers began at a young age, as she dug in and planted alongside her father in their family garden, growing healthy, beautiful blooms, every year. The indispensable lessons she learned then--and those she has since picked up from master gardeners--form the best practices she applies to her voluminous flower gardens today. For the first time, she compiles the wisdom of a lifetime spent gardening into a practical yet inspired book. Learn how and when to plant, nurture, and at the perfect time, cut from your garden. With lush blooms in hand, discover how to build stunning arrangements."--